635. Efficacy, Pharmacokinetics (PK), and Safety Profile of MEDI3902, an Anti-Pseudomonas aeruginosa Bispecific Human Monoclonal Antibody in Mechanically Ventilated Intensive Care Unit Patients; Results of the Phase 2 EVADE Study Conducted by the Public-Private COMBACTE-MAGNET Consortium in the Innovative Medicines Initiative (IMI) Program. (31st December 2020) - Chastre, Jean; François, Bruno; Bourgeois, Marc; Komnos, Apostolos; Ferrer, Ricard; Rahav, Galia; De Schryver, Nicolas; Lepape, Alain; Koksal, Iftihar; Luyt, Charles-Edouard; Garcia, Miguel Sanchez; Torres, Antoni; et al.
Abstract: Background: Pseudomonas aeruginosa (PA) pneumonia is associated with morbidity and mortality in mechanically ventilated, intensive care unit (MV ICU) patients despite best clinical care. We assessed efficacy, PK, and safety of MEDI3902 in MV ICU subjects in the placebo-controlled, randomized Phase 2 EVADE study (NCT02696902; EudraCT 2015-001706-34). Methods: Subjects with PCR-confirmed PA colonization of the lower respiratory tract were randomized to either a single IV infusion of 1, 500 mg MEDI3902 (n = 85) or placebo (n = 83). Primary Efficacy endpoint was Endpoint Adjudication Committee-determined relative risk reduction (RRR) of PA pneumonia incidence in MEDI3902 vs. placebo recipients within 21 days post dose (2-sided α = 0.2). Serum MEDI3902 PK levels were measured through 49 days post dose. Treatment-emergent adverse events (TEAEs) and serious AEs (SAEs) were assessed through 49 days post dose. Results: Baseline characteristics were similar between groups. MEDI3902 did not meet the primary endpoint of PA pneumonia vs. placebo (22.4% vs. 18.1%; RRR -23.7%, P = 0.491). Mean serum MEDI3902 level was 9.46 µg/mL (target 1.7µg/mL) at 21 days post dose, with a t½ 5.6 days. Proportion of subjects with TEAEs was similar between groups: ≥1 TEAE (98.8% MEDI3902; 97.6% placebo); ≥1 serious; and/or ≥grade 3 severity SAE (70.6% MEDI3902; 66.3% placebo). Deaths were numerically higher, although not statistically significant (24 (28.2%) MEDI3902 vs 19 (22.9%) Placebo; RRR -23.3%, P 0.429). Post-hoc analyses suggested RRR 47% among ~70% of the study population who had baseline Procalcitonin levels < 0.55 µg/L (12.5% MEDI3902 vs 23.7% placebo; 80%CI 6.1%-69.9%; P 0.135). Similarly, RRR 83% was observed among 50% of study subjects with baseline absolute neutrophil count (ANC) of < 8170 /µL (2.8% MEDI3902 vs 17.0% placebo; 80%CI 39.5%-95.5%; P 0.038). Subjects with Procalcitonin < 0.55 µg/L and ANC < 8170/ µL also had higher serum PK exposure. Conclusion: A single IV dose of MEDI3902 provided PK exposure above the target level but did not achieve primary efficacy endpoint of reduction in PA pneumonia. Efficacy trends were observed in subjects with lower levels of baseline inflammatory biomarkers. MEDI3902 may have a path forward in certain patient populations such as ICU patients with lower baseline inflammation. Disclosures: Jean Chastre, MD, AstraZeneca (Scientific Research Study Investigator) Marc Bourgeois, MD, AstraZeneca (Scientific Research Study Investigator) Apostolos Komnos, MD, PhD, AstraZeneca (Scientific Research Study Investigator) Ricard Ferrer, MD, PhD, Shionogi B.V. (Advisor or Review Panel member) Galia Rahav, MD, AstraZeneca (Scientific Research Study Investigator) Nicolas De Schryver, MD, AstraZeneca (Scientific Research Study Investigator) Alain Lepape, MD, AstraZeneca (Scientific Research Study Investigator) Miguel Sanchez Garcia, MD, PhD, AstraZeneca (Scientific Research Study Investigator) Antoni Torres, MD, PhD, AstraZeneca (Scientific Research Study Investigator) Omar Ali, PhD, AstraZeneca (Employee) Kathryn Shoemaker, MS, AstraZeneca (Employee) Alexey Ruzin, PhD, AstraZeneca (Employee, Shareholder) Yu Jiang, PhD, AstraZeneca (Employee) Susan Colbert, BSN, AstraZeneca (Employee) Drieke Vandamme, PhD, AstraZeneca (Scientific Research Study Investigator) Terramika Bellamy, n/a, AstraZeneca (Employee) Colin Reisner, MD, AstraZeneca (Employee) Filip Dubovsky, MD, MPH, AstraZeneca (Employee) Hasan S. Jafri, MD, FAAP, AstraZeneca (Employee)